The integration of Artificial Intelligence (AI) into education has transformed language learning practices, particularly through the emergence of ChatGPT as an intelligent conversational tool. For Health Administration students, English grammar plays a crucial role in developing professional communication skills required for administrative documentation, healthcare reporting, policy writing, and international collaboration. ChatGPT offers opportunities to enhance grammar learning through interac - Devi Nurhastuti; Nanda Pambudi; Ape Segenil (Science and Education Journal (SICEDU), 2026)
The integration of Artificial Intelligence (AI) into education has transformed language learning practices, particularly through the emergence of ChatGPT as an intelligent conversational tool. For Health Administration students, English grammar plays a crucial role in developing professional communication skills required for administrative documentation, healthcare reporting, policy writing, and international collaboration. ChatGPT offers opportunities to enhance grammar learning through interactive explanations, personalized feedback, and autonomous learning experiences tailored to learners' academic and professional needs. However, its implementation also raises pedagogical and ethical concerns regarding response accuracy, learner dependence, and academic integrity. This critical literature review discusses the theoretical foundations of English grammar learning for Health Administration students, explores the educational potential of ChatGPT, critically examines its pedagogical implications, and identifies challenges and future directions for AI-assisted grammar instruction.